Pelatihan Pembuatan Dimsum Ikan Sebagai Upaya Pemberdayaan Masyarakat Kampung Mentigi - Ruslan, Ruslan; Sanstya Fatma Melati; Melani; Deo Irwan Saputra, Deo; Annisa Rizka Pratiwi; Widya Yuningsih; Ayu Nurul Desafitri; Fadila Ashari; Agun Suherly; Kamaruzaman (Jurnal Pengabdian dan Pemberdayaan Masyarakat Kepulauan Riau (JPPM Kepri), 2024)
Mentigi Village, Tanjung Uban Kota Village, North Bintan District, Bintan Regency, Bintan, precisely Mentigi Village is one of the areas where most of the people are fishermen. The results of community fishermen can be in the form of selar, swordfish, benggol, red cob, white cob, kaci, red-eye fish. The village is very abundant. However, the seafood lack processing of marine products by the Mentigi village community so that with this KKN activity, a work program was sparked in accordance with the related theme, namely local wisdom. This research aims to encourage community creativity in processing marine products to increase the economic income of the people of Mentigi village.The approach used in this research is the ABCD approach with the method used in this study is qualitative descriptive. The author uses a qualitative descriptive approach. Qualitative, descriptive descriptive research is a problem formulation that directs researchers to explore or capture social situations that will be studied thoroughly, broadly, in detail and in depth. From the research, it can be concluded that this training has caused interest in processing dim sum products to be managed into marine products of the Mentigi village community. This cob dimsum is also a legacy for the community to increase profit from income escalation for the prosperity of Mentigi Village